AL-FĀRĀBĪ’S SYNTHESIS: PLATO, ARISTOTLE, AND THE SHAPING OF ISLAMIC PHILOSOPHY - Hafizah, Fithri Dzakiyyah; Kharisman, Hadi (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2024)
The discourse surrounding Islamic philosophy has garnered significant attention among scholars, highlighting a multitude of benefits and limitations related to its authenticity and its position as an essential component of Islamic cultural legacy. Some believe that Islamic philosophy is simply a reinvention of Greek philosophical concepts, thus undermining its credibility. Conversely, proponents advocate the integration of Greek philosophical principles with Islamic tenets as a synthesis rather than a simple replication. This article aspires to delve into these diverse perspectives by analyzing the historical transformation of Islamic philosophy, with a spotlight on its initial periods, particularly stressing the impact of Abū Naṣr al-Fārābī (d. 951 CE), a significant figure in Islamic philosophy who synthesized Greek philosophical ideas, notably those of Aristotle and Plato, to construct a unique Islamic philosophical framework. Through a qualitative conceptual analysis, this article evaluates the authoritative dimensions and philosophical disputes between Aristotle and Plato, particularly concerning ontology and epistemology, while accentuating al-Fārābī’s endeavors to harmonize their philosophical positions. This article suggests that al-Fārābī engaged in a critical examination of both Plato's and Aristotle’s perspectives on universal truth and human cognition, which ultimately led him to incorporate their philosophies into a unique Islamic framework.